A randomised controlled feasibility trial of the Graded Repetitive Arm Strengthening Programme delivered to survivors of stroke at home. (2nd August 2020) - Dodzo, Wilson; Grant, Robert; Forsyth, Leigh; Ramdharry, Gita M
Abstract : Background/aims: This randomised controlled feasibility trial evaluated the recruitment, engagement and effect of the Graded Repetitive Arm Strengthening Programme in a community rehabilitation setting in London, UK. Methods: A parallel design was used to ascertain the effect of the Graded Repetitive Arm Strengthening Programme plus standard care compared to standard care only over four weeks. Eleven participants were randomised using permuted blocks randomisation following discharge, with six participants allocated to the Graded Repetitive Arm Strengthening Programme (study) group and five to the standard care (control) group. The primary outcome was the Wolf Motor Function Test. Secondary outcomes were the Motor Activity Log and grip strength. Results: A total of five participants in each group were analysed as one person withdrew from the study group. Participants in the study group gave more time to supplementing their exercise time independently (160% more vs 42% more). Most Wolf Motor Function Test tasks' time and function data showed a small difference in favour of the Graded Repetitive Arm Strengthening Programme. Results were re-examined using a Bayesian structural equation model to quantify changes in the underlying impairment. This showed significant differences: 40% faster task completion ( P <0.001, 95% confidence level [CI] 30–49%), mean improvement of 0.54 on the five-point functional ability score ( P <0.001, 95% CI 0.39–0.68), odds ratio of 0.05 for non-completion of task ( P <0.001, 95% CI 0.02–0.14). Conclusions: This study has shown that implementing the Graded Repetitive Arm Strengthening Programme is feasible and may have a greater effect on outcomes when delivered as part of care in a community rehabilitation setting. The analysis of the Wolf Motor Function Test was also critiqued.